Analisis PIECES Sistem Pembayaran Pajak Elektronik Menurut Persepsi Wajib Pajak di KPP Pratama Jakarta Cakung Satu: PIECES, Tax Payment Electronic System, System Quality - Rudi, Rudi (Politeknik Ganesha Medan, 2019)
The General Directorate of Taxation attemped to realize the taxpayer’s aspirations with simplifying the tax payment procedure both monthly taxes and annual taxes by applying the electronic tax payment system (e-billing).e-billing is electronic paying methode with billing code (which is 15 code number) issued by tax billing system. This research is using qualitative research method with descriptive approach which is picturing electronic paying system fairness with PIECES (Performance, Information, Economy, Control, Efficiency, and Service) by tax payer reseption in Pratama Cakung I Tax Office. The research showing the quality of electronic tax paying system in Pratama Cakung I Tax Office, with Service Variable found to be the best by the tax compare to Performance, Information, Economy, Control, and Efficiency. Overanl PIECES analysis from the elektronik tax paying system in Pratama Cakung I Tax Office showing electronic tax paying system base on Performance, Information, Economy, Control, Efficiency and Service is excelent.